A study on factors influencing the adoption of internet banking - Mohd Fadzillah, Nur Farizan; Sapian, Muhamad Arsyad (2014)
Internet banking has become the latest delivery channel for banking services due to the reaction from globalization and liberalization of financial services. This research mainly focuses on factor influencing the adoption of internet banking services. The factor that we study is attitude, perceived behavioral control, awareness and convenience towards the intention to use internet banking. Besides, this study also examined whether or not there is a correlation between respondents demographic elements and their adoption of internet banking. In completing this research, survey were utilized, random sampling method was used. The sample for this study drawn from UiTM Malacca City Campus citizen. This study revealed that attitude was the factor that lead people use internet banking. In contrary, awareness is the major factor of why people are not using internet banking. Some recommendations and suggestion were given that could help in rapid migration of people to internet banking, resulting in considerable adoption of internet banking.